2007
DOI: 10.1038/nature06100
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA control of Nodal signalling

Abstract: MicroRNAs are crucial modulators of gene expression, yet their involvement as effectors of growth factor signalling is largely unknown. Ligands of the transforming growth factor-beta superfamily are essential for development and adult tissue homeostasis. In early Xenopus embryos, signalling by the transforming growth factor-beta ligand Nodal is crucial for the dorsal induction of the Spemann's organizer. Here we report that Xenopus laevis microRNAs miR-15 and miR-16 restrict the size of the organizer by target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
136
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(139 citation statements)
references
References 33 publications
1
136
0
2
Order By: Relevance
“…So far, studies linking miRNAs to Wnt signaling in various contexts have only investigated a limited number of miRNAs because of predefined hypotheses relating to specific miRNAs (Martello et al, 2007;Kapinas et al, 2009) or a limited capacity (o100 miRNAs) of the analytical platform utilized . In this study, we explored a considerably larger repertoire of miRNAs (n ¼ 664), and found the levels of numerous miRNAs to change following dnTCF4 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, studies linking miRNAs to Wnt signaling in various contexts have only investigated a limited number of miRNAs because of predefined hypotheses relating to specific miRNAs (Martello et al, 2007;Kapinas et al, 2009) or a limited capacity (o100 miRNAs) of the analytical platform utilized . In this study, we explored a considerably larger repertoire of miRNAs (n ¼ 664), and found the levels of numerous miRNAs to change following dnTCF4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The regulatory mechanism was not further defined, but a subsequent study suggested that it depended on modulation of Notch activity (Herranz et al, 2008). In another developmental setting, ectopic stimulation of Wnt signaling in Xenopus laevis frog embryos led to decreased miR-15/-16 levels (Martello et al, 2007). Levels of miR-29 family members were reported to increase during Wnt-induced differentiation of mouse and human osteoblast bone cells in vitro (Kapinas et al, 2009(Kapinas et al, , 2010, and miR-30e levels increased during differentiation of rat intestinal cells in a beta-catenin/TCF4-dependent manner (Liao and Lonnerdal, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Early frog development is specified by nodal signaling, and the spatial restriction of the embryonic cells that respond to nodal is regulated by two members of the miR-15 family, miR-15 and miR-16, which target the ActRII receptor mRNA (Martello et al 2007). The expression of the same type II receptor can be down-regulated by miR-181a in granulosa cells of the ovary, which differentiate in response to activin (Zhang et al 2013b); activin signaling represses miR-181a expression so that its type II receptor can be expressed at significant levels that promote granulosa cell differentiation.…”
Section: Control Of Tgf-b Receptor Expression By Micrornasmentioning
confidence: 99%
“…In Xenopus laevis, the asymmetry of nodal signaling is partially regulated by two microRNAs (miRNAs), miR-15 and miR-16. These miRNAs are enriched at the ventral side of the embryo and attenuate the nodal signaling gradient by targeting the nodal Roof plate induction (BMP-4 and BMP-7) Anterior neural tissue specification (BMP-5 and BMP-7) Dorsoventral patterning of the nervous system (BMP-4, BMP-6, and BMP-7) Neurogenesis (BMP-2, BMP-4, and BMP-6) Astrocytogenesis (BMP-2 and BMP-4) Cholinergic neuron specification (BMP-9) Guidance of commissural axons (BMP-7) Dendritic growth Neuronal migration Induction of neurotrophin dependence Apoptosis of stem/progenitor cells Nodal Induction of nervous system Induction of floor plate Differentiation of hypothalamic neurons Activins Induction of nervous system Specification of rod photo receptors GDFs Neurogenesis in olfactory epithelium receptor activin receptor type 2A (ACVR2A, also known as ActRII) (Martello et al 2007). Zebrafish use a different miRNA, miR-430, to target nodal signaling (Choi et al 2007).…”
Section: Neural Inductionmentioning
confidence: 99%